2006
DOI: 10.1523/jneurosci.3192-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Fractalkine/CX3CL1 Negatively Modulates Active Glutamatergic Synapses in Rat Hippocampal Neurons

Abstract: We examined the effects of the chemokine fractalkine (CX3CL1) on EPSCs evoked by electrical stimulation of Schaffer collaterals in patch-clamped CA1 pyramidal neurons from rat hippocampal slices. Acute application of CX3CL1 caused a sustained reduction of EPSC amplitude, with partial recovery after washout. CX3CL1-induced EPSC depression is postsynaptic in nature, because paired-pulse ratio was maintained, amplitude distribution of spontaneous excitatory postsynaptic currents shifted to lower values, and whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 63 publications
14
99
1
1
Order By: Relevance
“…Both constitutive and stimulated fractalkine cleavage would ultimately limit activation of microglia and support neuronal survival as previously reported (5)(6)(7)(8)(9)(10). Evidence indicates that fractalkine provides a tonic inhibitory signal that controls neighboring microglia resulting in reduced release of pro-inflammatory cytokines and increased production of neurotrophins (41); it controls glutamatergic activity by inhibiting excitatory postsynaptic currents (6,25,42); it negatively regulates neuronal migration while promoting their adhesion to ECM (43). The extent to which each of these mechanisms is involved in the physiological role of fractalkine may vary at different stages of life and/or during disease states.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Both constitutive and stimulated fractalkine cleavage would ultimately limit activation of microglia and support neuronal survival as previously reported (5)(6)(7)(8)(9)(10). Evidence indicates that fractalkine provides a tonic inhibitory signal that controls neighboring microglia resulting in reduced release of pro-inflammatory cytokines and increased production of neurotrophins (41); it controls glutamatergic activity by inhibiting excitatory postsynaptic currents (6,25,42); it negatively regulates neuronal migration while promoting their adhesion to ECM (43). The extent to which each of these mechanisms is involved in the physiological role of fractalkine may vary at different stages of life and/or during disease states.…”
Section: Discussionmentioning
confidence: 67%
“…The relative expression of these chemokines and their receptors by neuronal and nonneuronal cells suggests a role for both SDF-1 and fractalkine in neuronal-glial communication, as supported by in vivo and in vitro evidence (3,23). Furthermore, data from different groups have shown that SDF-1 and fractalkine are both involved in neuroprotection and regulate excitatory neurotransmission (6,24,25). However, while the neuroprotective effect of fractalkine seems to be related to its ability to counteract microglia-induced neurotoxicity, SDF-1 can directly protect neurons via the activation of its specific receptor CXCR4, which is coupled to major survival pathways, such as the phosphoinositide 3-kinase (PI3K)-Akt pathway (26,27).…”
mentioning
confidence: 85%
“…We and others have previously shown that (i) CX 3 CL1 modulates glutamatergic AMPA-currents revealed as a reduction of the amplitude of both synaptic and agonist-evoked currents; (ii) CX 3 CL1 action on AMPA-currents is stringently and specifically related to the activation of CX 3 CR1 (2,8,32). In this study, we provide evidence that CX 3 CL1-induced depression of AMPA-currents in hippocampal neurons is suppressed by a specific antagonist of AR 1 , DPCPX.…”
Section: Discussionmentioning
confidence: 91%
“…Since we have found that the neuroprotective action of CX 3 CL1 on hippocampal neurons is dependent on AR 1 activation, we were interested to investigate whether AR 1 could be also involved in the previously described CX 3 CL1-induced neuromodulation (2,8). We report that the CX 3 CL1-mediated inhibition of the amplitude of AMPA-currents in cultured hippocampal neurons was abolished by DPCPX treatment.…”
Section: Dpcpx Inhibits CX 3 Cl1-and Bv2-st Medium-mediated Ampa-currmentioning
confidence: 97%
“…It is important to note that although many of these effects may be a result of deficient synaptic pruning, they can also be ascribed to a microglial effect on neuronal circuit activity via other mechanisms in response to soluble CX3CL1 (Ragozzino et al, 2006). A more recently described pathway for microglial pruning is the complement system (Stevens et al, 2007), in which weaker synaptic inputs on developing neurons are decorated with C1q and C3 molecules capable of engaging CR3 receptors on microglia for targeted elimination (Schafer et al, 2012;Stevens et al, 2007).…”
Section: The Brain-resident Immune Systemmentioning
confidence: 99%